Gaya Kepemimpinan Kepala Desa pada Kinerja Aparatur Desa: Studi Kasus di Desa Susuk, Kecamatan Tiganderket, Kabupaten Karo - Br Surbakti, Via Maharani; Jamil, Bahrum; Sembiring, Walid Musthafa (Mahesa Research Center, 2024)
The leadership style of the village head is very important to the performance of the village apparatus because one of the factors that influence performance is the leadership style. The purpose of this study was to determine the leadership style of the Village Head on the performance of the Village Apparatus, to determine the performance of the Village Apparatus and the inhibiting factors of the Village Head's leadership style. The problems are the lack of human resources seeing how important roles and responsibilities are in providing services to the community but have not been able to respond optimally to community needs, inadequate facilities and infrastructure and some village officials are still late coming to the office and even leaving the village office. Before working hours end. To approach this problem, the theoretical reference from Rivai includes authoritarian, democratic, and laissez-faire leadership styles and aspects from Dwiyanto which include productivity, service quality, responsiveness, responsibility, and accountability. Data were collected based on data collection techniques with observation, interviews and documentation, and analyzed qualitatively with a descriptive nature. The results showed that the leadership style used by the Village Head was a democratic leadership style seen from the decision making the Village Head always held deliberation, the Village Head was also very open to criticism and suggestions, the ability of the Village Head to motivate the Village Apparatus and the communication that was established with the two village heads. Direction. It's just that there are still inhibiting factors in improving the performance of the apparatus, namely the lack of Human Resources, inadequate facilities and infrastructure and the low level of discipline of the Village Apparatus.